ANALISIS IMPLEMENTASI KEBIJAKAN PROGRAM SEKOLAH AMAN BENCANA BANJIR DI SMP NEGERI 1 DAYEUHKOLOT KABUPATEN BANDUNG - Endang Komara; Deding Ishak; Sobari Sobari; Saofanita Saofanita; Fitria Sukmawati Kusnadi; Nikmatul Khoiriyah Khoiriyah (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of the Flood Disaster-Safe School Program (SPAB) at SMP Negeri 1 Dayeuhkolot, focusing on the aspects of planning, organizing, actuating, and controlling (POAC), infrastructure readiness, students’ life skills development, as well as supporting and inhibiting factors. This research employed a qualitative approach using a case study method. Data were collected through observations, interviews, and documentation involving the principal, teachers, and students. The findings indicate that the implementation of the flood disaster-safe school policy has been carried out fairly well and systematically. The school has developed flood contingency plans, established a disaster preparedness team, conducted evacuation drills, and integrated disaster mitigation into the learning process. The program has positively contributed to improving school community preparedness and enhancing students’ life skills, such as cooperation, independence, and adaptability. However, the implementation still faces challenges, including limited infrastructure, budget constraints, insufficient teacher training, and suboptimal evaluation mechanisms. Overall, the SPAB policy plays an important role in fostering a culture of disaster preparedness and strengthening school resilience.